Large ventral hernias: to drain… And what to drain… That is the question!. Issue 10 (1st September 2021) - Idrees, Marwan; Mare, Hans; Lester, Leanne; Kariyawasam, Sanjeeva
Abstract: Background: Drain placement is common practice in repair of ventral hernias, specifically complex hernias. There is little‐to‐no evidence for benefit of drains and best practice in‐terms of number, position, duration of use and type of drains. This study investigates drain profile in open repair of large ventral hernias. Methods: A retrospective two‐centres audit with data collected via electronic and paper‐based medical records from the 1 February 2015 to 29 June 2020. All elective and emergency cases were included. Main outcomes included surgical site infection (SSI), seroma and hematoma formation. Results: A total of 186 patients included, out of those 128(68.5%) had drain placed. Drain placement had a higher incidence of SSI (20.3% in drain group and 15.5% in no drain group), however, drains were more likely to be placed in complex ventral hernias. Drain practice varied significantly between surgeons, however, there was a clear trend to higher SSI rates with longer duration of drain use (specifically longer than 5 days, p ‐value: 0.05) and higher drain output on removal (specifically higher than 150 ml/24 h, p ‐value 0.004), furthermore, prolonged use did not decrease risk of seroma formation. Drain position, number of drains and suction pressure did not affect seroma or SSI rates. Conclusion: Our data suggests no clear benefits of drain usage in most ventral hernia repairs. Prolonged drain use led to higher risk of SSI and did not decrease rate of seroma formation. If used, we recommend use of short drain duration<5 days. Further RCTs to evaluate drain placement in large ventral hernias are needed. Abstract : Correlation of duration of drain (in days) with daily percentage of SSI(surgical site infection) and seroma formation.